المحتوى اللغوي في كتاب اللغة العربية السنة أولى متوسط الجيل الثاني تحليل نماذج من النصوص - يخي شريف, صابرية (كلية الأدب العربي والفنون, 2025)
تناولت في هذا البحث الموسوم ب:" المحتوى اللغوي في كتاب اللغة العربية للسنة أولى متوسط الجيل الثاني-تحليل نماذج من النصوص-" إلى الكشف عن مدى انسجام المحتوى اللغوي مع المستوى المعرفي للتلاميذ في هذه المرحلة الدراسية، والمنهج المعتمد في هذا البحث هو المنهج الوصفي، وجاءت خطة البحث على النحو التالي مقدمة وبعدها مدخل تطرقت فيه إلى مفهوم المحتوى اللغوي ومفهوم تحليل المحتوى وكذلك مفهوم الجيل الثاني وبعد ذلك الفصل الأول النظري الذي قسمته إلى مبحثين تطرقت في المبحث الأول إلى مبادئ ومعايير اختيار المحتوى وكذلك الى طرق اختيار المحتوى وتنظيمات، وفي المبحث الثاني قدمت مبادئ وشروط وأهداف تحليل المحتوى وكذلك أهمية تحليل محتوى الكتب المدرسية أما الفصل الثاني التطبيقي قد تطرقت فيه إلى مبحثين في المبحث الأول قمت بتحليل نموذجين من كتاب اللغة العربية للسنة الأولى متوسط-الجيل الثاني- أما المبحث الثاني أنجزت تحليلا للاستبيانات الأساتذة والتلاميذ ودرست نتائج الاستبيان. وأخيرًا خاتمة اشتملت النتائج المتواصل عليها في هذا البحث مع بعض توصيات والاقتراحات. Language Textbook for First-Year Middle School – Second Generation: An Analysis of Selected Texts”, aims to explore the extent to which the linguistic content aligns with the cognitive level of students at this stage of education. The study adopts a descriptive methodology The structure of the research is as follows: an introduction, followed by a preface in which the concepts of linguistic content, content analysis, and the second-generation curriculum are discussed The first chapter (theoretical) is divided into two sections: the first deals with the principles and criteria for content selection, as well as methods and approaches for organizing content; the second addresses the principles, conditions, and objectives of content analysis, along with the importance of analyzing school textbooks. The second chapter (practical) also includes two sections. The first presents an analysis of two sample texts from the Arabic language textbook for first-year middle school – second generation. The second presents an analysis of questionnaires completed by teachers and students, followed by a discussion of the results.Finally, the conclusion summarizes the main findings of the study and offers several recommendations and
Keywords: : المحتوى اللغوي، الجيل الثاني، تحليل المحتوى.